Hydrothermal synthesis and characterization of visible-light-driven Mo-doped Bi2WO6photocatalyst - Phattranit Dumrongrojthanath (2018)
© 2018 The Ceramic Society of Japan. All rights reserved. In this research, Bi2WO6nanoplates doped with 0, 1, 3 and 4% by weight of Mo were successfully synthesized by hydrothermal method. X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and ultravioletvisible spectroscopy certified that the as-synthesized products were uniform orthorhombic Bi2WO6nanoplates with absorbance of the pure product in ultraviolet region and of the doped ones in both ultraviolet and visible regions. Photocatalysis of the products was also evaluated through the degradation of rhodamine B under visible light irradiation. The Bi2WO6nanoplates doped with 3% by weight of Mo have the highest rate constant of 0.023 min11.